A utopia de Ivan Illich - Leonídio, Adalmir; Leão Neto, Edson Pereira de Souza (Diálogos Latinoamericanos, 2019)
This essay seeks to reflect on Ivan Illich’s criticism of the structural problems of capitalism in the 1970s and the elaboration of a utopian thought that is an alternative to modern industrial society. It is based on his long experience as a missionary in Latin America and the problems generated in this backward pole of world capitalism.